Cooperative lane control application for fully connected and automated vehicles at multilane freeways. (February 2020) - Khattak, Zulqarnain H.; Smith, Brian L.; Park, Hyungjun; Fontaine, Michael D.
Highlights: Develop a prototype cooperative lane control (LCS) application for connected and automated vehicles under multiple platoons. The novel concept represents the future of Active Traffic Management and replaces traditional gantry deployed LCS. Analyze the operational impacts of cooperative lane control in terms of improvement in freeway throughput. Utilize the concept of volatility to infer variations in acceleration and deceleration regimes with CAVs. Abstract: Advances in communications technology have made the development of connected and automated vehicle (CAV) applications that may potentially replace traditional, gantry operated lane control signals (LCSs) possible. This paper develops the concept of a prototype CAV-enabled LCS application and provides a preliminary assessment of the potential improvement it offers over traditional LCS. Real-world data obtained from an LCS on I-66 in Northern Virginia was used to calibrate and validate a baseline simulation model. Further, the current lane control scenarios utilized in the Northern Virginia LCS were identified and relevant data resulting from implementation of those scenarios were collected to model the LCS in a simulation environment. The performance of real-world LCS was then compared to a prototype CAV-enabled LCS application developed in this research. The CAV-enabled LCS application consistently outperformed the traditional LCS with increased throughput and speeds. On average, an increase of 18.4%, 9.6% and 12.8% in throughput was observed for three selected scenarios under the best case of a 1 sec headway. Furthermore, the CAV-enabled LCS application was also found to reduce volatility, represented by variation in acceleration and deceleration regimes, by an average of 25.6% and 49.6%. The reduction in turbulence in the traffic stream may indicate potential improved safety with the CAV system.